Pengaruh Latihan Squat Jump dan Burpees terhadap Tinggi Lompatan saat Melakukan Teknik Jump Shoot pada Pemain Handball Kota Malang - Dimas Wicaksono; Artifa Sorraya (Universitas Insan Budi Utomo, 2023)
Sport is an important activity that must be done by humans in order to obtain a healthy body, one of which is handball or handball. The game of handball is currently popular with all groups, even though it sounds rare, but now many are starting to get to know the game of handball. Handball is popular not only among students who play it, but now it has spread to students from the junior high school level to the upper secondary level. This is shown from the existence of competitions held in each region. The purpose of this study, among others, was to find out: the effect of squat jump training on jump height when performing jump shoot techniques for handball players in Malang, the effect of burpees on jump height when doing jump shoot techniques for handball players in Malang, the difference between the effect of squat jump training and burpees on the height of the jump when performing the jump shoot technique on handball players in Malang. This research uses the type of experimental research. The design of this study used an experimental design (true experimental design) with the design type Two Group Pretest and Posttest Design, namely the experimental design was carried out in two different groups (experimental group 1 and experimental group 2) which received different exercises (squat jump exercise and exercise burpees). There is no difference in the effect of squat jump and burpees exercises on jump height when performing the jump shoot technique for handball players in Malang. This can be proven based on the results of calculating the mean difference between the two experimental groups, where the t test value of the research test is 0.121, with db = 42, the critical t value is 1.681. From these results it shows that the price of the t-statistic is 0.121